2018
DOI: 10.1080/03019233.2018.1482599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium olivine on the mineral structure and compressive strength of pellets

Abstract: To study the effect of magnesium olivine on the compressive strength, phase composition and mineral structure of magnetite pellets, six groups of pellets were prepared by changing the content of olivine and the pellets were further subjected to the preheating and roasting processes in tube furnaces. Scanning electron microscopy-Energy dispersive spectrometer (SEM-EDS), X-Ray diffraction (XRD) and Mercury injection apparatus were used to characterise the microstructure and porosity of pellets. Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When the MgO-bearing flux content increased from 0% to 2%, the porosity of roasted pellets was increased from 18.61% to 24.06%. The increased porosity deteriorated the CCS of MgO-bearing pellets [49][50][51][52]. Moreover, MgO could activate the decomposition of haematite, reducing the decomposition temperature and accelerating the decomposition rate.…”
Section: Cold Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…When the MgO-bearing flux content increased from 0% to 2%, the porosity of roasted pellets was increased from 18.61% to 24.06%. The increased porosity deteriorated the CCS of MgO-bearing pellets [49][50][51][52]. Moreover, MgO could activate the decomposition of haematite, reducing the decomposition temperature and accelerating the decomposition rate.…”
Section: Cold Compressive Strengthmentioning
confidence: 99%
“…Fan et al reported that when the MgO content of the pellets is 2.0%, the CCS improved by 1500 N pel −1 with the basicity increasing from 0.1 to 0.4 and the CCS increased by 700 N pel −1 with the B content increasing from 0% to 0.6% [56].
Figure 5. SEM diagrams of pellets with different magnesium olivine contents [52].
…”
Section: Study On Metallurgical Properties Of Flux Pelletsmentioning
confidence: 99%